Sulfonamides as Potential Bioactive Scaffolds - Khan, Farhan A.; Mushtaq, Sidra; Naz, Sadia; Farooq, Umar; Zaidi, Asma; Bukhari, Syed M.; Rauf, Abdur; Mubarak, Mohammad S. (Current Organic Chemistry, 2018)
Sulfonamides are compounds with a broad spectrum of biological applications, and can act as potential medicinal molecules in drug discovery and drug development. Numerous sulfonamide-based molecules can be used to develop potent lead compounds with better efficacy and less toxicity. This review focuses on the latest information pertaining to sulfonamide derivatives having different pharmacological properties including anticancer, antiviral, antimicrobial, antibacterial, antifungal, antiinflammatory, antituberculosis, carbonic anhydrase inhibition, antimalarial, antiparasitic, anticonvulsant, and antidepressant activities, as well as carbonic anhydrase inhibitors. Relevant references have been obtained from MEDLINE (PubMed), Google Scholar, ScienceDirect, Cochrane, Scopus, SID, SciFinder, and ISI Web of Knowledge. This review article provides a literature overview of the various biological activities of sulfonamides, and covers the related literature from the last decade. It also briefly describes the therapeutic importance of sulfonamide derivatives and their pharmacological applications in a concise manner.
Keywords: anticancer